2017
DOI: 10.1007/s00268-017-4107-3
|View full text |Cite
|
Sign up to set email alerts
|

Survival Benefits of Surgical Resection in Patients with Recurrent Biliary Tract Carcinoma

Abstract: Surgical resection for recurrent BTC may prolong survival in highly selected patients. A hepatectomy might offer a survival benefit for patients with a solitary liver metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…In an observational study, 5‐year survival rates were 45% for 13 cases of hepatectomy for metachronous liver metastases from biliary tract cancer and 0% for nine cases of unresectable liver metastases 17 . Motoyama et al also reported 5‐year OS rates of 40% after hepatectomy in 15 patients and 7% in 16 patients who had chemotherapy alone and concluded that hepatectomy can improve the prognosis in selected patients 18 . All of these are retrospective, case‐observation studies, and a strong selection bias is likely involved; nevertheless, hepatectomy might be effective treatment for highly selected patients with metachronous liver metastases from biliary tract cancer who fulfill certain strict criteria.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In an observational study, 5‐year survival rates were 45% for 13 cases of hepatectomy for metachronous liver metastases from biliary tract cancer and 0% for nine cases of unresectable liver metastases 17 . Motoyama et al also reported 5‐year OS rates of 40% after hepatectomy in 15 patients and 7% in 16 patients who had chemotherapy alone and concluded that hepatectomy can improve the prognosis in selected patients 18 . All of these are retrospective, case‐observation studies, and a strong selection bias is likely involved; nevertheless, hepatectomy might be effective treatment for highly selected patients with metachronous liver metastases from biliary tract cancer who fulfill certain strict criteria.…”
Section: Resultsmentioning
confidence: 99%
“…Hepatectomy for liver metastases from these primaries cannot be recommended even if an R0 resection is achievable. There may be a few exceptions, such as three or fewer metachronous tumors smaller than 3‐5 cm developing >2 years after the resection of the primary site 15–18 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations